2017
DOI: 10.1007/s10974-017-9474-8
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin treatment suppresses SERCA1b levels independently of other players of calcium homeostasis in C2C12 myotubes

Abstract: Follistatin (FS) is a high affinity activin-binding protein, neutralizing the effects of the Transforming Growth Factor-beta (TGF-β) superfamily members, as myostatin (MSTN). Since MSTN emerged as a negative regulator, FS has been considered as a stimulator of skeletal muscle growth and differentiation. Here, we studied the effect of FS administration on the Ca-homeostasis of differentiating C2C12 skeletal muscle cells. FS-treatment increased the fusion index, the size of terminally differentiated myotubes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…As the percentage of GalC + area was higher in the tri-cultures than in cultures supplemented with exogenous activin-A, and as this percentage was reduced nonetheless at the same level by follistatin than in exogenous activin-A supplemented cultures, we concluded that activin-A was required but did not induce OPC differentiation alone. Supporting this hypothesis is the fact that as follistatin is mostly known to inhibit activin-A, it also inhibits factors from the TGF superfamily such as the bone morphogenic proteins [56]. It may be hypothesized that SCAP produce other essential bioactive molecules that stimulate OPC differentiation along with activin-A, the actions of which are also inhibited by follistatin.…”
Section: Discussionmentioning
confidence: 99%
“…As the percentage of GalC + area was higher in the tri-cultures than in cultures supplemented with exogenous activin-A, and as this percentage was reduced nonetheless at the same level by follistatin than in exogenous activin-A supplemented cultures, we concluded that activin-A was required but did not induce OPC differentiation alone. Supporting this hypothesis is the fact that as follistatin is mostly known to inhibit activin-A, it also inhibits factors from the TGF superfamily such as the bone morphogenic proteins [56]. It may be hypothesized that SCAP produce other essential bioactive molecules that stimulate OPC differentiation along with activin-A, the actions of which are also inhibited by follistatin.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in wild-type C2C12 cells, the growth stimulator follistatin, an antagonist of the muscle growth inhibitor myostatin, selectively suppressed Ca 2+ uptake and SERCA1b expression. This indicates that SERCA1b is tightly coupled with stages of ongoing differentiation [ 101 ]. The expression pattern of MLN, the first discovered regulin [ 62 ] mirrors that of SERCA1b [ 94 ].…”
Section: Serca1b: a Grey Eminencementioning
confidence: 99%
“…C2C12 cells, derived from mice myoblasts, have been used as model cell lines for the study of cell differentiation and muscle functions in vitro (Fodor et al, 2017;Rahar et al, 2018;Rapizzi et al, 2008;Soltow et al, 2013). By differentiation induction of C2C12 cells, a large subpopulation of myoblasts forms elongated polynuclear myotubes, while a subpopulation of the cells, called reserve cells, remains undifferentiated ( Fig.…”
Section: Introductionmentioning
confidence: 99%